2010
DOI: 10.1007/s12274-010-0032-6
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-like bilayer hexagonal silicon polymorph

Abstract: We present molecular dynamics simulation evidence for a freezing transition from liquid silicon to quasi-twodimensional (quasi-2D) bilayer silicon in a slit nanopore. This new quasi-2D polymorph of silicon exhibits a bilayer hexagonal structure in which the covalent coordination number of every silicon atom is four. Quantum molecular dynamics simulations show that the stand-alone bilayer silicon (without the confinement) is still stable at 400 K. Electronic band-structure calculations suggest that the bilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 40 publications
4
55
0
Order By: Relevance
“…The past three years have witnessed a burst in silicene research: Single-layer silicene (SLS) has been experimentally grown on Ag(111) and other substrates [5][6][7][8][9][10][11][12][13][14][15][16][17] . Multilayer silicene (MLS) also draws intensive attentions, e.g., in chiral superconducting behavior 18 , valley-polarized quantum Hall effect 19 , and dramatically tunable electronic structure by varying stacking modes 20,21 . By now, MLS films have been grown by several groups on Ag(111) using molecular beam epitaxy (MBE) [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…The past three years have witnessed a burst in silicene research: Single-layer silicene (SLS) has been experimentally grown on Ag(111) and other substrates [5][6][7][8][9][10][11][12][13][14][15][16][17] . Multilayer silicene (MLS) also draws intensive attentions, e.g., in chiral superconducting behavior 18 , valley-polarized quantum Hall effect 19 , and dramatically tunable electronic structure by varying stacking modes 20,21 . By now, MLS films have been grown by several groups on Ag(111) using molecular beam epitaxy (MBE) [22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Unlike bilayer graphene, whose most stable structure is AB (Bernal) stacking with van der Waals interlayer interactions, BLS nanosheet has been predicted to have a wide variety of morphologies due to the possible interlayer covalent bonds. [17][18][19][20] For instance, the common used theoretical BLS model also has AB stacking mode with half of the Si atoms connected by interlayer covalent bonds. For example, Yao et al found this structure holds interesting electronic properties such as chiral superconducting behavior.…”
mentioning
confidence: 99%
“…Despite the extensive studies on monolayer silicene [15][16][17][18][19][20], the investigation on multilayer silicene is far from its sufficiency. Although a few theoretical investigations have been performed on the freestanding bilayer silicene [21][22][23][24], the mechanism for the relative stability among the obtained phases has not been understood.…”
mentioning
confidence: 99%